On the mitigation potential and urban climate impact of increased green infrastructures in a coastal mediterranean city. (1st August 2022) - Khan, Ansar; Papazoglou, Eleni G.; Cartalis, Constantinos; Philippopoulos, Kostas; Vasilakopoulou, Konstantina; Santamouris, Mattheos
Abstract: An increase of the green infrastructure (GI) in cities contributes to sharing the common goals of reducing energy usage, mitigating pollution emissions, and improving the urban climate. The synergy between urban heat island (UHI) and extreme urban heat in Athens (Greece), during the summer, is inevitable, while its green cover is considerably low. However, very few studies have reported the biophysical effects of the GI on the surface standard meteorological field and urban boundary layer (UBL) that are triggered by changes in the GI at a seasonal scale. The present study sheds light on the complex synergies between UHI and extreme urban heat focusing on warm coastal cities like Athens.To this end, we hypothetically designed and simulated three scenarios of increased GI, such as GI30, GI50, and GI70. The mosaic approach is used, and the portion of each urban grid cell is replaced with different types of vegetation patches, by 30%, 50%, and 70% using the weather research and forecasting (WRF) model, coupled with a single-layer urban canopy model (SLUCM) at city-level for assessing mitigation potential and urban climate impact. The results showed that the daily peak decrease of the ambient temperature at 17:00LT is close to 0.0157 °C per unit of increase of the GI, while the maximum expected daytime summer temperature decrease is 0.7 °C, 1 °C, and 1.1 °C for GI30, GI50, and GI70 scenarios respectively compared to the control case. The corresponding decrease of the nighttime ambient temperature is found to be 0.0375 °C per unit of increase of the GI, whereas the maximum temperature reduction for the G70 scenario is close to 1.9 °C. Increased GI is found to significantly lower the height of the planetary boundary layer (PBL), thus increasing the risk of higher pollution concentration, while a significant impact on the strength of the sea breeze and the level of humidity is observed increasing the risk of thermal discomfort. Results are also compared with the findings of thirty similar projects from other cities to provide a global assessment of the mitigation potential of additional GI in cities. Our results contribute significantly to understanding the mitigation potential and urban climate impact of increased GIs at a seasonal scale. Graphical abstract: Image 1 Highlights: Green infrastructure may decrease peak daily temperature by 0.0157 °C per unit of increase. Per unit increase of the green infrastructure may decrease peak night temperature by 0.0375 °C. Increase of the green infrastructure decrease the height of planetary boundary layer up to 600 m.